Stroke-Related Mortality at Different Altitudes: A 17-Year Nationwide Population-Based Analysis From Ecuador - Ortiz-Prado, Esteban; Espinosa, Patricio S.; Borrero, Alfredo; Cordovez, Simone P.; Vasconez, Jorge E.; Barreto-Grimales, Alejandra; Coral-Almeida, Marco; Henriquez-Trujillo, Aquiles R.; Simbaña-Rivera, Katherine; Gomez-Barreno, Lenin; Viscor, Gines; Roderick, Paul (Frontiers in Physiology, 2021)
Introduction: Worldwide, more than 5.7% of the population reside above 1,500m of elevation. It has been hypothesized that acute short-term hypoxia exposure could increase the risk of developing a stroke. Studies assessing the effect of altitude on stroke have provided conflicting results, some analyses suggest that long-term chronic exposure could be associated with reduced mortality and lower stroke incidence rates. Methods: An ecological analysis of all stroke hospital admissions, mortality rates and disability-adjusted life years in Ecuador was performed from 2001-2017. The cases and population at risk were categorized in low (<1,500m), moderate (1,500m -2,500m), high (2,500m -3,500m) and very high altitude (3,500-5,500m) according to the place of residence. The derived crude and direct standardized age-sex adjusted mortality and hospital admission rates were calculated. Results: A total of 38,201 deaths and 75,893 stroke-related hospital admissions were reported. High altitude populations (HAP) had lower stroke mortality in men (OR: 0.91 [0.88 - 0.95]) and women (OR: 0.83 [0.79 - 0.86]). In addition, HAP had a significant lower risk of getting admitted to the hospital when compared with the low altitude group in men (OR: 0.55 [CI95% 0.54 - 0.56]) and women (OR: 0.65 [CI95% [0.64 - 0.66]). Conclusions: This is the first epidemiological study that aims to elucidate the association between stroke and altitude using four different elevation ranges. Our findings suggest that living at higher elevations offers a reduction or the risk of dying due to stroke as well as a reduction in the probability of being admitted to the hospital. Nevertheless, this protective factor has a stronger effect between 2,000m to 3,500 m.